Prevalence of bovine fascioliasis, areas at risk and ensuing losses in the state of Goiás, Brazil - De Aquino, Fernanda Martins; Soares, Vando Edésio; Rossi, Gabriel Augusto Marques [UNESP]; Nicaretta, João Eduardo; De Bastos, Thiago Souza Azeredo; Cruvinel, Leonardo Bueno; Couto, Luiz Fellipe Monteiro; De Cavalcante, Alliny Souza Assis; Felippelli, Gustavo [UNESP]; Cruz, Breno Cayeiro [UNESP]; Maciel, Willian Giquelim [UNESP]; Gomes, Lucas Vinicius Costa [UNESP]; et al. (FapUNIFESP (SciELO), 2018)
The present study had to determine the prevalence and spatial distribution of areas at risk of bovine fascioliasis in the state of Goiás, central-western Brazil between 2007 and 2014; to evaluate the associations of some epidemiological variables with occurrences of Fasciola hepatica in animals; and to estimate the economic losses that this parasite on the cattle industry. It could be concluded that of 23,255,979 animals slaughtered, the average prevalence of F. hepatica in cattle in Goiás during the period evaluated was 0.0026% (95% CI: 0.0024-0.0028). In the State of Goias, in about then years (since when this parasite was found for the first time by other researchers in 2007), F. hepatica was diagnosed in 168 new municipalities. Using the regression analysis, the effective bovine herd size was a significant risk factor (OR= 1.21; 95% CI 1.1022-1.4510; p ≤ 0.05) for cattle to be infected with fascioliasis in the state of Goiás. The cattle-rearing industry lost approximately R$ 15,072.75 (US$ 4,785) due to condemn of livers with Fasciola in the state of Goiás. New studies need to be conducted in these regions, with the aim to identify the likelihood of presence of intermediate hosts, which might serve as a source of F. hepatica infection for definitive hosts.
Prevalência de fasciolose bovina, áreas de risco e perdas subsequentes no estado de Goiás, Brasil
Keywords: Cattle; Epidemiology; Fasciola hepatica; Maps; Spatial distribution; Zoonosis